A case series on post-COVID pulmonary rehabilitation: Early experiences from Kerala, South India - Akhilesh Kunoor,; Aditya Ashok,; Merlin Moni,; Asmita Mehta,; Elizabeth Mary Thomas,; Veena Viswan,; K Harikrishnan, (Indian Journal of Case Reports, 2020)
Patients who were contracted with COVID-19 are reported to have a variety of symptoms affecting neuromuscular, psychological, cardiac, and respiratory systems. A significant proportion of patients present with prolonged symptoms even weeks to months including minor illness. The lung is the most common and important organ affected in COVID-19 and sequela can result in exertional breathlessness, cough, hypoxia, or pulmonary fibrosis. Along with medical and supportive therapy, a multidisciplinary pulmonary rehabilitation program is essential to improve the quality of life and reduce symptoms in post-COVID-19 patients. We report a case series of three cases who presented with diverse manifestations after COVID-19 recovery, who were treated with a multidisciplinary pulmonary rehabilitation program. This case series, with early experiences from Kerala which had its peak of COVID-19 pandemic in late October 2020, shows a substantial improvement of symptoms in patients even with initial rehabilitation sessions itself, which shows promising hope in post-COVID-19 management.